Fenomena Self-Reward dalam Budaya Konsumerisme Digital : Studi Literatur tentang Tren Gen Z di Media Sosial - Jihan Nafilah; Desy Safitri; Sujarwo Sujarwo (PT. Intelek Cendikiawan Nusantara, 2025)
Currently, Generation Z is actively promoting the “self-reward” trend on social media. Self-reward is a form of self-recognition for achievements in the workplace or academic success. Examples of self-reward include vacations, dining out, watching movies, shopping, and more. Self-reward can serve as a reason for Generation Z to adopt a consumerist attitude when using social media. The purpose of this study is to investigate whether the phenomenon of self-reward can lead Generation Z to become consumerist on social media. The research method employed a qualitative approach using literature review. Self-reward can be seen as a reason for Generation Z to shop on social media, often without realizing they are engaging in excessive consumerism. Therefore, to prevent consumptive behavior, one must use social media wisely and prioritize needs over desires.